2021
DOI: 10.1177/1759720x21998508
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sarcopenia on rehabilitation outcomes after total knee replacement in older adults with knee osteoarthritis

Abstract: Introduction: Knee osteoarthritis (KOA) is associated with an increased risk of sarcopenia, and aging-related muscle deterioration continues after total knee replacement (TKR). Low skeletal muscle mass index may influence postoperative rehabilitation outcomes. Through this study, we aimed to investigate the impact of preoperative sarcopenia on clinical outcomes after postoperative rehabilitation in older Asian adults. Methods: A total of 190 older adults (39 men, 151 women) were enrolled from two previous tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Recovery in knee ROM following TKR is likely to be negatively impacted by either obesity [93,96] or sarcopenia [98]. In agreement with prior findings, survival analysis results in the current study demonstrated that the obesity group took a time period of 7 weeks longer than the non-obese control did to recover a knee flexion over 125 degrees.…”
Section: Sarcopenic Obesity and Its Risk Of Poor Recovery In Range Of Motion After Total Knee Replacementsupporting
confidence: 91%
“…Recovery in knee ROM following TKR is likely to be negatively impacted by either obesity [93,96] or sarcopenia [98]. In agreement with prior findings, survival analysis results in the current study demonstrated that the obesity group took a time period of 7 weeks longer than the non-obese control did to recover a knee flexion over 125 degrees.…”
Section: Sarcopenic Obesity and Its Risk Of Poor Recovery In Range Of Motion After Total Knee Replacementsupporting
confidence: 91%
“…Preoperative functional status predicts the function outcome [26], muscle mass in people with Osteoarthritis is associated with greater impairment [27]. Liao et al [19] ] studied the impact of preoperative extremity skeletal muscle reduction of 190 elderly KOA patients in Taiwan on the clinical rehabilitation results after TKA, indicated that skeletal muscle reduction was negatively correlated to the WOMAC-Function, chair experiments, walking pace test. However, there is no research concentrated on muscle mass of surgical legs to rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle muss loss was also observed after TKA by Hopkins et al [18]. Sarcopenia independently had negative impacts on the rehabilitation of physical mobility after TKA [19], early postoperative training of lower limb muscle strength can promote function recovery [6,20].…”
Section: Introductionmentioning
confidence: 99%
“…Effect of sarcopenia on the results of total knee arthroplasty in patients with osteoarthritis Due to the fact that sarcopenia is often common in patients with osteoarthritis, researches are being conducted to study the dynamics of the recovery period after total knee arthroplasty. There are two prospective studies showing that after total hip or knee arthroplasty in patients with sarcopenia the length of hospital stay is increased, the percentage of complications, falls, fractures of the lower extremities, and repeated hospitalization are increased [33][34][35].…”
Section: Searching For Associations Between Sarcopenia Sarcopenic Obesity and Osteoarthritis In Population Studiesmentioning
confidence: 99%
“…There is a study of the effect of sarcopenia on the clinical outcome after surgery in patients with knee OA [35]. The authors revealed that patients with sarcopenia had worse WOMAC-PF scores compared to patients without sarcopenia, in addition, the severity of pain in patients with sarcopenia according to the WOMAC scale was more severe.…”
Section: Searching For Associations Between Sarcopenia Sarcopenic Obesity and Osteoarthritis In Population Studiesmentioning
confidence: 99%